Performance da aplicação de polímero no tratamento de sementes de amendoim - Furlani, Ana Caroline Ferreira Athayde [UNESP] (2009)
Due to the importance of the peanut culture in Jaboticabal region and to the necessity of increase its production technology, the objective of the present work was to evaluate the possibility of to utilize the film-coating technique in this culture seeds. It was realized three assays: a) in laboratory relating to the effect of the treatment on peanut seeds germination and vigor, b) in greenhouse relating to seeds germination in infested soil with Rhizoctonia solani and c) in the field assay relating to the influence of treatment on culture production. It was utilized two peanut seed lots of Runner IAC 886 cultivar with high and low vigor. Seeds received the following treatments: control, Laborsan® film-coating (2,0 mL.kg-1 seeds), fungicide Fludioxonil (Maxin XL) – (1,5 mL.kg-1 seeds) recovered with the Laborsan® film-coating (2,0 mL.kg-1 seeds) and fungicide Fludioxonil (Maxin XL) – (1,5 mL.kg-1 seeds). Seeds vigor level had effect in all evaluations. The film-coating used in this work did not affect peanut seeds physiological potential and either the fungicide efficiency, showing a promising technique, however, it must had utilized only with fungicide because it does not control soil pathogens.